2021
DOI: 10.35848/1347-4065/ac148b
|View full text |Cite
|
Sign up to set email alerts
|

Bragg coherent diffraction imaging allowing simultaneous retrieval of three-dimensional shape and strain distribution for 40–500 nm particles

Abstract: We report the improvement of an apparatus for Bragg coherent X-ray diffraction imaging (Bragg-CDI) at BL22XU in SPring-8 to expand the applicable particle size and the application of the Bragg-CDI technique for Pd and ferroelectric barium titanate (BaTiO 3 ) fine crystals with particle sizes of 40-500 nm. Preparing a vacuum environment around the sample enabled us to obtain the high-contrast diffraction pattern of a 40 nm particle. The reconstructed three-dimensional image showed the outer shape, size, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The CXD experiment was performed on the apparatus developed for the coherent X-ray diffraction imaging 26,29) installed at BL22XU of SPring-8. 30) A liquid-nitrogen-cooled Si(111) DCM monochromatized X-rays from an in-vacuum undulator.…”
Section: Coherent X-ray Diffraction Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CXD experiment was performed on the apparatus developed for the coherent X-ray diffraction imaging 26,29) installed at BL22XU of SPring-8. 30) A liquid-nitrogen-cooled Si(111) DCM monochromatized X-rays from an in-vacuum undulator.…”
Section: Coherent X-ray Diffraction Measurementsmentioning
confidence: 99%
“…The energy was tuned to 8 keV (λ = 1.5498 Å). The heating holder was mounted on a vacuum chamber, 26) in which the mounting holder is compatible with other membrane holders. 26) The X-rays were focused by a refractive lens (Karlsruhe Institute of Technology) 31) to typically 2.9(6) × 2.00(3) (vertical × horizontal) μm 2 , with a focal length of 1.0 m. The sample indicated by the red arrow in Fig.…”
Section: Coherent X-ray Diffraction Measurementsmentioning
confidence: 99%
“…The acceleration voltage was 200 kV. The Bragg-CDI was carried out on the coherent X-ray scattering station installed at BL22XU of SPring-8. The incident X-ray energy was set to 8 keV. The Pb 0.82 Sr 0.18 VO 3 particles were mounted onto a STEM grid (ELS-C10, Okenshoji) with a laminated structure consisting of a 15–20 nm-thick polymer, 20–25 nm-thick C, and 25 μm-thick Cu sheets.…”
Section: Methodsmentioning
confidence: 99%
“…Copyright © 2012 Springer Nature. BaTiO 3 , (BT) is a representative lead-free piezoelectric material that has been studied for a long time for the grain size effect [31][32][33][34], crystal structure at the atomic and electron level [35][36][37], nanoparticles [38][39][40], and texturing [41,42], and it is still being actively performed even to this day. Recently, Liu and Ren et al suggested in 2009 that Ca and Zr co-doped BT (BZT-BCT) has the potential to replace the PZT system [43].…”
Section: Lead-free Piezoelectricsmentioning
confidence: 99%